Two new species and records of Olophrum laxum species group (Coleoptera: Staphylinidae: Omaliinae: Anthophagini) from China and Nepal - Shavrin, Alexey V. (Zootaxa, 2018)
Two new species of the genus Olophrum Erichson, 1839 of the laxum group are described and illustrated: O. lama Shavrin, sp.n. (Nepal: Rolwaling Himal) and O. schuelkei Shavrin, sp.n. (China: Shaanxi). Olophrum laxum Shavrin & Smetana, 2017 from Yunnan and O. pacei Shavrin & Smetana, 2017 from Shaanxi and Hubei provinces of China are recorded for the first time. A modified key of the laxum group is provided.